Identification of the Use and Utilization of Information Technology for the Residents of Tegalrejo Berbah Sleman Yogyakarta - Nugraheny, Dwi (SENATIK STT Adisutjipto, 2018)
The usage Information Technology of smartphones is increasingly prevalent in various parts of the world, especially the Indonesian people themselves are competing to buy the latest type of smartphone because of user dissatisfaction with the smartphone features offered. This can be seen through users of various ages, ranging from children, teenagers to adults. Likewise for the residents of the Tegalrejo area, the use of information and communication technology has become popular in the community. The purpose of this study was to identify the results of data processing using and utilizing information technology via smartphone by the people of Berbah Sleman Tegalrejo using the quicksort method. Identification results to find out the use and utilization of information technology through smartphones with features that have been used effectively and efficiently by the residents of Tegalrejo Berbah Sleman so as to make a digital literacy community.